Jamu Tradisional, Minuman Instan Upaya Edukasi Jamu Instant Dengan Metode Demonstrasi Untuk Ibu Duta Besar Dunia di Filipina - Mauren Gita Miranti; Nurul Farikhatir Rizkiyah; Sri Handajani; Lucia Tri Pangesthi; Annisa Nur’Aini (Universitas Negeri Surabaya, 2025)
Jamu is a traditional Indonesia drink made from a variety of natural ingredients, including spices, herbs, and other natural ingredients. Jamu has a long history and is an important part of the tradition of health and folk medicine in Indonesia. Jamu is part of Indonesia's cultural heritage. Introducing jamu to the world can help increase appreciation for Indonesia's culture and its contribution to global knowledge. This article explores the Institute's efforts in educating and modernizing herbal medicine to gain wider acceptance, especially globally. The purpose of this study is to: introduce jamu as Indonesia's cultural heritage by educating participants on how to properly process ready-to-drink and instant jamu. This research was conducted by presentation, demonstration, and question and answer methods. The results of the study showed that 1) participants who were ambassadors from several countries in Asia, America, and Europe responded positively to jamu as Indonesia's cultural heritage. In general, herbal medicine is preferred as a drink, but they prefer herbal medicine without added sugar. Participants also found out that spices and plants that are considered wild can be processed into drinks that have medicinal properties, and 2) a demonstration using two techniques for making herbal medicine, namely the boiling technique for ready-to-drink herbal medicine and the crystallization technique for instant herbal medicine which has a longer shelf life.